National libraries: The emergence of a new national/public library approach - Eiman Alshamari (IFLA Journal, 2026)
Globally, 351 national libraries (NLs) and 406,487 public libraries (PLs) operate following the International Federation of Library Associations and Institutions (IFLA) guidelines. However, a hybrid model has emerged – the national/public library (NPL) – where NLs function fully as PLs while retaining their national status. Despite the existence of over 30 NPLs worldwide, a significant research gap remains regarding formal recognition and standardised guidelines for this approach. This study explores the characteristics, successes and challenges of the NPL model through the perspectives of 26 participants from 26 countries. Using Classical Grounded Theory, the research identifies success factors, such as budget efficiency and public approachability, alongside barriers like role tension and the absence of clear frameworks. The findings address these gaps by proposing practical guidelines for international organisations, including IFLA, Conference of Directors of National Libraries, and United Nations Educational, Scientific and Cultural Organization. These guidelines aim to facilitate global adoption, positioning NPLs as vital pillars for both national heritage and community engagement.